Optimisation of ammonia refrigeration system by manipulating parameters of vapour compression cycle. (26th February 2021) - Azhar, Aashir; Ibrahim, Uzair; Rafiq, Luqman; Shahdab, Fareeha; Farrukh, Sarah; Hussain, Arshad
Energy saving is the key to reduce the operational cost of any industrial process. Slight optimisation of the process can lead to reduced energy consumption and higher profits. In this study, the ammonia refrigeration cycle has been optimised by changing some of the process conditions. The demand of ammonia has been reduced to 1.30%, lowering the cooling water temperature for the same cooling load. Moreover, the co-efficient of performance (COP) of the cycle has also increased from 4.0 to 4.68. The CoolPack® software has been used to determine the maximum possible COP of ammonia along with the analysis and design of the ammonia refrigeration cycle. The study also encompasses a detailed comparison of potential refrigerants and proposes R32 as a potential alternative in industrial refrigeration systems ensuring higher efficiency, safety, and environmental friendliness.